The Analysis of Figurative Language In The Movie: Spellbound - Erna Pranata Putri (Asosiasi Dosen Muda Indonesia, 2025)
Since words may be used to link individuals, express ideas, and transmit meaning, they are essential to communication. Character development, plot development, and audience involvement are all influenced by the language employed in dialogue. Through the use of figurative language, characters can communicate complex ideas, emotions, or relationships in dialogue in ways that are rich in meaning, vivid, and memorable. The purpose of this study is to identify the types of figurative language used in the Spellbound film. This film was analyzed using Gorys Keraf's theory of figurative language. The figurative language found were metaphor (23), antonomasia (14), personification (9), pun (8), irony (6), simile (4), antithesis (4), and hyperbole (30). The use of figurative language in the dialogue of the film Spellbound makes the story more interesting.